Access routes to high mountain huts facing climate-induced environmental changes and adaptive strategies in the Western Alps since the 1990s. Issue 4 (8th August 2019) - Mourey, Jacques; Ravanel, Ludovic; Lambiel, Christophe; Strecker, Joël; Piccardi, Mattia
ABSTRACT: In the European Alps, high mountain environments are subject to major impacts resulting from climate change, which strongly affect human activities such as mountaineering. The purpose of the study was to examine changes in access routes to 30 high mountain huts in the Western Alps since the 1990s. Data were derived from the use of two different methods, geo-historical studies and a questionnaire, and were used to identify both the climate-related processes affecting the climbing routes and the strategies implemented by public entities, Alpine clubs, guide companies, and hut keepers to maintain acceptable safety and technical conditions. The case studies revealed issues affecting three access routes and the results from the questionnaire showed that the main processes affecting access routes were loss of ice thickness and retreat from the front of the glaciated areas. Commonly, in situ equipment was installed to facilitate access for mountaineers and/or a part of a route was relocated to a safer area. The authors conclude that in most cases, the measures were effective but they were limited by financial, ethical and legal issues, especially in protected or classified areas that could jeopardise their durability and effectiveness.